49x99简便计算为什么

49x99 =49x(99+1)-49 =4900-49 =4851

解:49X99-51 =49X99+49-51-49 =49X(99+1)-100 =4900-100 =4800 满意请采纳.

49x99+49=49*(99+1)=49*100=4900

原式=49*(100-1)=4900-49=4851 原式=(50-1)*99=4950-99=4851

=49乘(99+1)=49乘100=4900

49(99+1)=490

解:49+99+49的简便计算如下:49+99+49=(50-1)+(100-1)+(50-1)=50-1+100-1+50-1=(50+100+50)-(1+1+1)=200-3=19749+99+49=197

99+49*99=99*(1+49)=99*50=(100-1)*50=100*50-50=5000-50=4950

49*99+49*98=49*(200-3)=(50-1)*(200-3)=50*200-200-150+3=10000-350+3=9653

相关文档

99乘49的简便方法计算
49x75+99简算
49x99简便计算脱式
99乘以49的简便运算
49x15一49x5简便运算
49x99十49x51
49x99十46简便计算
99乘49加99的算便算法
jinxiaoque.net
ppcq.net
fpbl.net
qwrx.net
krfs.net
电脑版